PENGGUNAAN MEDIA REALIA TERHADAP HASIL BELAJAR SISWA KELAS IV SDN 1 SIDOKATON - Lestari, Yulita Dwi; Kurniasih, Try Indiastuti; Rahayu S., Evi (STKIP PGRI Bandar Lampung, 2019)
This study aims to determine the use of media realia in science learning. The object of this research is fourth grade students of SDN 1 Sidokaton with 10 students. This type of research is classroom action research. Data collection techniques use test results of learning and observation. Data technique is done through quantitative and qualitative, to test the effectiveness of using N-gain. The results of this study indicate that the use of realia media can improve student learning outcomes in science subjects.